THE ROLE OF CELEBRITY ENDORSEMENT AND ONLINE CUSTOMER REVIEWS OF PURCHASE INTENTION OF MAKE OVER COSMETIC PRODUCTS WITH PURCHASES ON SHOPEE THROUGH BRAND TRUST AS AN INTERVENING VARIABLE - Suryananda, Triska Marta; Mahmud, Mahmud; Amron, Amron; Pakarti, Piji (Universitas Dian Nuswantoro, 2025)
This study analyzes the effect of celebrity endorsement and online customer review on purchase intention of Make Over cosmetic products, with brand trust as an intervening variable on the Shopee platform. The research is based on the growing consumption of cosmetics through e-commerce and the crucial role of public figures and consumer reviews in influencing buying intentions. The study employs a quantitative method using the Partial Least Square (PLS) approach and purposive sampling of 126 respondents who have purchased Make Over products via Shopee. The results show that celebrity endorsement and online customer review have a significant positive effect on brand trust, which in turn affects purchase intention. Both factors also have an indirect effect through brand trust. These findings highlight the importance of building brand trust through appropriate endorser selection and active management of consumer reviews.